The impacts of COVID-19-induced online lectures on the teaching and learning process: An inquiring study of junior secondary schools in Orlu, Nigeria - Nneji, Confidence Chioma; Urenyere, R.; Ukhurebor, Kingsley Eghonghon; Ajibola, Saheed; Onaseso, Olatunji Oluwatosin (Frontiers in Public Health, 2022)
This study investigated how the sudden shift in the system of learning during the COVID-19 pandemic impacted the students, how the external environment impacted their performance, and the structural barriers encountered, which equally had significant impacts on students at junior secondary schools (JSS) in Orlu, Imo State, Nigeria. The study adopted the descriptive survey research method. The simple random sampling method was adopted with a sample size of 650 students. The data were collected using a structured questionnaire, rated using a four-point Likert scale, and analyzed using descriptive statistics such as frequency counts, percentages, and means. 60.10, 58.80, 59.50, 59.00, and 59.50% of the respondents agreed to research questions respectively. Based on these results, it was concluded that the COVID-19-induced online teaching and learning impacted negatively on the students and on the process of teaching and learning due to inadequate prior preparation for such a system of teaching and learning at the JSS level within the study area. These have serious implications and remain significant for policy and practice in the education sector.